(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The diagnostic journey in healthcare, from sample collection to diagnosis, relies heavily on the collaborative efforts of lab technicians and nurses. This article explores the crucial roles of these professionals in ensuring accurate diagnoses and effective patient care.